Sistemas colaborativos baseados em wikimapas: uma análise sob o ponto de vista do Modelo 3C - Borges , Carlos E. L.; Reis, Me. Adriana Neves dos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
The development of wikimaps based groupwares represents big challenges in its analysis, design and implementation. The development of the project Buracos Monitor, a platform to mark holes in the road, and its repercussion has allowed to experience the challenges about specifying requirements, components and other needs of this kind of solution. The goal of this research is to build a set of recommendations and best practices for the analysis and design of this type of system, exposing common problems and solution proposals, compiled as a framework. Correlated systems were analyzed, from the point of view of the 3C Collaboration Model (Communication, Coordination, Cooperation), using methods proposed on the RUP-3CGroupware. As results, a set of identified components are presented and classified based on the 3C Model. These results are proposed as fundamental and introductory knowledge for analysts, developers and designers interested in develop wikimaps based groupwares.